Removal of lead from industrial wastewater using a low cost waste material - Amer, Hayam Ahmed Talaat (AUC Knowledge Fountain, 2015)
Several industries utilize heavy metals in their industrial processes, eventually discharging them in their wastewater. Water contamination by heavy metals is a major environmental problem due to their acute toxicity and their accumulation in food chains. Therefore, intensive research work has been carried out lately on the feasibility of various low cost materials for the removal of heavy metals from wastewater. The main objective of the current research was to examine the potential of a low cost material for the removal of Pb2+ from a synthetic lead solution. The research work was divided into three core phases. Phase I was a preliminary comparative study among various agricultural wastes; sugarcane bagasse, rice straw and rice husk, two industrial wastes, namely cement kiln dust (CKD) and marble powder, and a natural material; lime. In Phase II the research was taken to a deeper level as the feasibility of utilizing rice straw for biosorption of Pb2+ was profoundly investigated using batch equilibrium experiments. The effect of several operating parameters on the uptake of Pb2+ was tested, which are the pH of the solution, contact time, rice straw dose, particle size, initial Pb2+ concentration and pre-treatment of rice straw. The percent removal of Pb2+ increased with increasing the pH, contact time, and rice straw dose up to the point of equilibrium; however, it decreased with the increase in the particle size. The pre-treatment of rice straw did not yield a considerable increase in the percent uptake of Pb2+. Langmuir and Freundlich isotherm models were used for the evaluation of the equilibrium experimental data; the correlation coefficients were 0.989 and 0.959, respectively. The maximum adsorption capacity of raw rice straw was calculated using Langmuir isotherm; 42.55 mg/g, which is higher than several adsorption capacities of rice straw reported in the literature. Phase III was conducting fixed-bed column experiments using rice straw. The service time of the columns and the treated volume of wastewater to breakthrough (Ce= 1mg/l) and to exhaustion (Ceâ‰ˆ 95% C0) increased with the increase in the bed depth of the packed rice straw; however, they decreased with the increase in the initial Pb2+ concentration and the flow rate of the solution. Physical and chemical characterization of rice straw was carried out in order to define the BET surface area, pore volume, average pore size, surface functional groups, shape of the cell wall and chemical composition. Biosorption of Pb2+ using rice straw was inferred to be due to a complex of physical and chemical mechanisms.